2016
DOI: 10.1038/srep39376
|View full text |Cite
|
Sign up to set email alerts
|

Senescence marker protein 30 (SMP30) serves as a potential prognostic indicator in hepatocellular carcinoma

Abstract: Senescence marker protein 30 (SMP30) has been identified as a tumor-related molecule of hepatocellular carcinoma (HCC). Its clinical significance and underlying mechanisms in HCC tissues, however, remain largely unexplored. We have demonstrated a preferentially expressed SMP30 in normal liver using a tissue microarray. By employing real-time quantitative PCR, two tissue microarrays and Oncomine database analysis, we have also shown that the SMP30 in HCC tissues has significantly reduced when compared with that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Studies have indicated that DCs pulsed with recombinant fusion proteins composed of an antigenic fragment and HSP protein can stimulate CTL [ 15 ]. The literature also shows that HSP90 can stimulate DCs and induce CTL polarization and activation [ 16 ]. A study showed that cross-presenting DCs is highly effective in inducing CTLs capable of eliminating liver cancer [ 17 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Studies have indicated that DCs pulsed with recombinant fusion proteins composed of an antigenic fragment and HSP protein can stimulate CTL [ 15 ]. The literature also shows that HSP90 can stimulate DCs and induce CTL polarization and activation [ 16 ]. A study showed that cross-presenting DCs is highly effective in inducing CTLs capable of eliminating liver cancer [ 17 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Although the role of SMP30 and its concomitant expression are well documented in other tumors, such as hepatocellular carcinoma [ 53 ], the relationship between SMP30 and mammary gland tumors still remains ambiguous and controversial. Sar et al reported that high SMP30 expression is noted in MCF-7 cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, SMP-30 serves as a prognostic marker and a potential therapeutic target for HCC. 14,15 It has been reported that SMP-30 expression is significantly reduced in HCC tissues compared with in adjacent non-tumor tissues and is negatively associated with the tumor size, TNM stage, and poor survival of HCC patients. 14 Silencing of SMP-30 promotes the proliferation and invasion of HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 It has been reported that SMP-30 expression is significantly reduced in HCC tissues compared with in adjacent non-tumor tissues and is negatively associated with the tumor size, TNM stage, and poor survival of HCC patients. 14 Silencing of SMP-30 promotes the proliferation and invasion of HepG2 cells. 15 Based on the antiaging effect of laminarin, we speculated that laminarin may upregulate SMP-30 expression.…”
Section: Introductionmentioning
confidence: 99%